El fondo minero del Archivo Histórico de la Escuela de Ingenieros de Lima (1876-1930) - Luque Luque, Juvenat (2007)
With the present anide it is sought to sliow the documental and inforsnative importunce that conserves the Historien! File ofthe School ofEngineers from Lima. O](f diversity of documents that conserves 11'é' will concentrare 0/1 the relative documents at the mining activitv uf/he Peru ofends ofthe .I:{X centurv ami beginniugs ofthe x.1' (JITe, (O have visitad tltis repository with this expressed purpose. This file is not unpublished becuusc it liad already been used before us by {he historian Ignacio Lope: Soria to edil Historv ofthe Nutiouul Univcrsitv ofEngineeriug. rile veorsfundacioualcs. U'(~\I-¡1Ihighligln tlieir minil/gfilllds as the nienioirs UI' field /'~'p(JrIS, the miuing' publicotions that it CI)I1.~t'I'1'I.'S, national andforeign bibliographical collections. product in their bigges: part of exchauges; offices metalúrgicas. miniug seuts, the technical services ofthe schoo! (O ,he miuing societv